Diagnosis of the Effectiveness of Pedagogical Processes for Meaningful Learning of Physics in High School: A Case Study at Unidad Educativa Aníbal San Andrés Robledo, Jaramijó, Ecuador : Estudio de caso en la Unidad Educativa Aníbal San Andrés Robledo Jaramijó, Ecuador - Alex; Arteaga Pita, Iván Gasendy (Revista Minerva, 2025)
Physics is an experimental science that seeks to explain all the phenomena of the universe. In Ecuador, the level of learning required in Physics reveals that the objectives set by the Ministry of Education for the subject in public institutions are not being achieved. This may be due to the inadequate use of teaching tools by educators. Moreover, many Physics teachers lack proper training and the necessary pedagogical skills to make the concepts relevant for students. The absence of effective teaching methods is a recurring issue, as Physics education often relies on memorization of formulas and theories without connecting this knowledge to practical or everyday applications. This not only hampers meaningful learning but also demotivates students, who fail to see the relevance of Physics in their daily lives. For this reason, the following research conducted a diagnostic assessment of Physics teaching for second-year high school students at Unidad Educativa Aníbal San Andrés Robledo. This was achieved through interviews with two teachers from the institution, observation of the development of three Physics classes, and the application of a test to measure student knowledge. The diagnostic results showed that in this educational institution, students do not achieve meaningful learning in Physics due to the ineffective application of teaching strategies, compounded by the teacher’s lack of adequate training. This underscores the need to develop a didactic strategy to achieve meaningful learning.